Chapter 22 Simulation Modeling as a Policy Tool - Furtado, Bernardo Alves (Taylor & Francis, 2023)
This chapter describes, justifies, presents the pros and cons of and illustrates the use of simulation modeling as a handy, cost-effective and agile tool for policymakers. Simulation modeling is flexible enough to accommodate different levels of detail, precision and time frameworks. It also serves the purpose of a concrete communication platform that facilitates scenario analysis, what-if alternatives and forward looking. We specifically define agent-based modeling within the larger simulation domain, provide a brief overview of other computation modeling methodologies and discuss the concepts of multiple models, verification, validation and calibration. The conceptual framework section closes with a discussion of advantages and disadvantages of using simulation modeling for policy at various stages of implementation. Finally, we present a panorama of actual applications of simulation modeling in policy, with an emphasis on economic analysis.